Δημιουργία ασύρματου συστήματος ελέγχου διαφόρων αισθητήρων σε κατοικίες - Σόλωνος, Σόλων (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This thesis title is “Design and creation of various wireless sensor control system in houses”. In this, the purpose of this work is analyzed and a study of existing market systems is done. Then, the company National Instruments is referred and its software LabView and hardware MyRIO which were used in the dissertation. Moreover the thermistor sensor, photocell, motor which were expected to be used in the system are analyzed. Then the connection of the sensors to MyRIO is explained and how they are connected to Smartphones or tablets with LabView programming. Finally, the virtual instruments of each sensor are explained and then there is a display of their work with photos.
Keywords: Wireless sensor control system; National instruments company; Thermistor sensor; Ασύρματο σύστημα ελέγχου αισθητήρων; Αισθητήρες θερμίστορ